Decision support for natural disasters and intentional threats to water security - NATO Advanced Research Workshop on Decision Support for Natural Disasters and Intentional Threats to Water Security (NATO science for peace and security series. Series C, Environmental security)
The NATO Advanced Research Workshop, “Decision Support for Natural Disasters and Intentional Threats to Water Security” was the result of close collaboration between environmental, security, water resource, and health officials in the United States and Croatia. The premise of the Workshop is that multiple, disparate threats to water security exist, and that shared decision support structures provide effective means for avoiding and responding to potential or actual situations. The Workshop was co-directed by Professors Tissa Illangasekare of the Colorado School of Mines, and Dragutin Geres of Hrvatske vode. The Workshop was organized into a series of case studies, presentation of management tools, or a combination of the two. Presentations were further organized as to (1) Natural Occurrences, (2) Anthropogenic Causes, and (3) Decision Support Tools. Delegates from eleven countries assembled to explore these topics at the Hotel Dubrovnik President in Dubrovnik from April 22–25, 2007. A total of thirty delegates from NATO, Partner, Mediterranean Dialog, or other countries were in attendance. The final program included technical sessions using a presentation and dialog format, a field trip, and networking sessions. There were twenty five technical presentations supported by seventeen formal papers (many updated in late-2008 and 2009), and these form the basis for these proceedings. Natural stressors and catastrophic events -- Impacts of the 2004 tsunami and subsequent water restorations actions in Sri Lanka -- Hurricane Katrina environmental and engineering concerns -- Sustainable water management and flood protection practices in Bulgaria -- Climate changes on natural hazards and water resources -- Antropogenic stressors -- Mapping of floods at the Slovak—Austrian section of the Morava River — Tool to improve decision support in crisis situation -- Drinking water security and health in Transylvania, Romania -- Strategies for the sustainable development in the Danube delta in Romania, Ukraine and Moldavia -- A database application integrated with GIS as a decision support tool for potentially polluted sites management as well as an overall water management -- Feasibility of early and emergency warning systems for safeguarding the transboundary waters of Armenia -- Decision support tools -- Water management in Croatia: what is at risk -- Water resource management problems in South Caucasus region -- Geoinformation support for water disaster situations -- Incorporation of the critical infrastructure management into the DSS on strategic water supply system management -- Groundwater vulnerability assessment using physical principles of contamination spreading -- Multiple criteria decision making and environmental security -- Service-oriented decision support governance -- An examination of ecological risk assessment at landscape scale and the management plan.